Glaciambulata neumayeri gen. et sp. nov., a new Antarctic trachymedusa (Cnidaria: Hydrozoa), with a revision of the family Ptychogastriidae - Galea, Horia R.; Roder, Cornelia; Walcher, Christoph; Warmuth, Marco; Kohlberg, Eberhard; Fischer, Philipp F. (European Journal of Taxonomy, 2016)
A new genus and species of sympagic trachymedusa, Glaciambulata neumayeri gen. et sp. nov., are described based on material from Antarctica. Its generic features are compared to those of its relatives, Ptychogastria Allman, 1878 and Tesserogastria Beyer, 1959, and a review of the family Ptychogastriidae Mayer, 1910, based on literature data, is provided. From this, it results that the poorly-known Pectis antarctica Haeckel, 1879, formerly assigned to Ptychogastria by a number of authors, displays all characters of the contemporary rhopalonematid genus Voragonema Naumov, 1971. It is additionally demonstrated that V. laciniata Bouillon et al., 2001 is coterminous with P. antarctica, a finding that clarifies, 137 years later, the morphology and the taxonomic status of Haeckel’s medusa. In accordance with the Principle of Priority, Pectis is recognized as the valid name of the genus, and Voragonema is assigned to its synonymy. Similarly so, the specific name introduced by Haeckel has priority over laciniata.